Barreiras n\~ao tarifárias ao comércio de produtos agropecuários brasileiros - Marcelo José Braga Nonnenberg; Gerlane Andrade; Helena Oliveira; Alice Saccaro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– In the last decades, it was observed a reduction in tariff barriers for all countries. Even though this reduction affected almost all goods, the agribusiness sector experienced a smaller impact, keeping a higher average tariff, relative to other industries. In addition to these tariff measures, the sector is also affected by a substantial number of non-tariff measures, which, depending on its nature, can be established as true barriers to international trade, affecting imports and exports. Thus, seeking to comprehend the present scenario about the imposition of non-tariff measures to agribusiness products on a global level, it was estimated a gravitational model through the Poisson pseudo maximum likelihood (PPML) estimator. This model was formulated based on the main agribusiness goods exported by Brazil, and also on the main measures groups, and the total: sanitary and phytosanitary measures (SPS), technical barriers to trade (TBTs) and measures related to exports. Those estimations were based on a panel database, built with data from the measures available from the United Nations Conference on Trade and Development (UNCTAD). The results suggest that there is not a clear relationship between the number of non-tariff measures with bilateral trade flows, generating positive and negative relations between those covariates, depending on the product analyzed. This result suggests that the relationship studied depends on the product analyzed and the kind of measure applied, showing the need for a deeper understanding of the data and a higher detailing on the classification of measures to fully comprehend the phenomenon.
Keywords: F13; F15; 330; non-tariff measures; gravitational model; farming sector products